Housing and Independent Living for Individuals with Intellectual and Developmental Disabilities - Leach, Debra (Journal of the American Academy of Special Education Professionals, 2016)
This manuscript provides a review of housing and independent living options for individuals with intellectual and developmental disabilities (I/DD). While there has certainly been an increased emphasis on community integration and inclusion for people with I/DD, barriers to delivering housing supports and services in natural, integrated settings still exist. An overview of the various housing options that are currently available for individuals with I/DD is provided followed by a discussion of the main themes related to promoting full community integration and funding sources that are available to support these efforts. This essential information will help special education teachers involved in delivering transition services and supports better plan with students and families as they consider independent living options upon graduation from high school.